Extra dimensions at the CERN LHC via mini-black holes: Effective Kerr-Newman brane-world effects - Rocha, R. da [UNESP]; Coimbra-Araújo, C. H. (American Physical Soc, 2006)
We solve Einstein equations on the brane to derive the exact form of the brane-world-corrected perturbations in Kerr-Newman singularities, using Randall-Sundrum and Arkani-Hamed-Dimopoulos-Dvali (ADD) models. It is a consequence of such models that Kerr-Newman mini-black holes can be produced in LHC. We use this approach to derive a normalized correction for the Schwarzschild Myers-Perry radius of a static (4+n)-dimensional mini-black hole, using more realistic approaches arising from Kerr-Newman mini-black hole analysis. Besides, we prove that there are four Kerr-Newman black hole horizons in the brane-world scenario we use, although only the outer horizon is relevant in the physical measurable processes. Parton cross sections in LHC and Hawking temperature are also investigated as functions of Planck mass (in the LHC range 1-10 TeV), mini-black hole mass, and the number of large extra dimensions in brane-world large extra-dimensional scenarios. In this case a more realistic brane-effect-corrected formalism can achieve more precisely the effective extra-dimensional Planck mass and the number of large extra dimensions-in the Arkani-Hamed-Dimopoulos-Dvali model-or the size of the warped extra dimension-in Randall-Sundrum formalism. © 2006 The American Physical Society.